Industrial Policies in Colombia - Marcela Melendez; Guillermo Perry (Inter-American Development Bank (IDB), 2010)
This paper surveys and analyzes industrial policies in Colombia, finding extensive use of productive development policies (PDPs) and despite claims of only moderate government intervention. Rarely explicitly associated with the need to address market failures, PDPs are instead associated with economic reactivation and vaguely defined competitiveness. There are also PDPs that address government failures considered unlikely to be corrected by first-best interventions. Colombia has made progress, however, in structuring an institutional setting for PDP design that is sufficiently linked with private sector groups to elicit information on constraints and opportunities that require government intervention. Nonetheless, the overall set of PDPs in place still lacks coherence and is not always guided by the policy requests of the private sector more widely defined.
Keywords: L52; L66; L67; L86; 330; Industrial policy; Productive development policy; Colombia